Pengaruh Permainan Edukasi Nutricard dalam Meningkatkan Kesadaran Remaja tentang Gizi Seimbang di UPT SMP Negeri 34 Gresik - Damayanti, Afinda Primadita; Rahma, Amalia (JGK: Jurnal Gizi dan Kesehatan, 2025)
This study aims to encourage the influence of the Nutricard educational game in increasing awareness of balanced nutrition in grade VIII students at UPT SMP Negeri 34 Kota Gresik. The study was conducted for one week in March 2025 with an experimental quantitative approach, using a pre-test and post-test design. The subjects of the study were 28 students selected through purposive sampling. The results showed a significant increase from the average pre-test score (75.71) to the post-test (87.32), as well as an increase in understanding of balanced nutrition from 75% to 96%. The results of the Paired Sample T-Test statistical test showed a t-count value = -60.060 and Sig. = 0.000 (p <0.05), proving that Nutricard had a significant effect on increasing students' understanding of balanced nutrition. Based on the questionnaire, most students stated that this educational game was more interesting and helpful in understanding the material than conventional learning methods. Therefore, it can be concluded that the Nutricard educational game is effective in increasing awareness of balanced nutrition in adolescents, so it is worthy of being used as an innovative learning media in schools.